Flexible Leadership and its Role in Achieving Academic Freedom in Government Universities (Journal of the College of Basic Education, 2025)
The current research seeks to identify flexible leadership and its role in achieving academic freedom in government universities. In order to achieve the research objectives, the researcher followed the descriptive correlational approach through a sample of university professors amounting to (150) professors from the University (Al-Mustansiriya, Baghdad, Iraq) according to a set of demographic variables, and in order to collect data and information, a questionnaire was designed consisting of two parts, the first on demographic variables and the second on the research variables, and after verifying the validity and reliability of the questionnaire and applying it to the current research sample, the study reached the following:- The results of the analysis provide valuable insights into the relationship between flexible leadership and academic freedom in government universities in Baghdad.- The results indicate a general positive perception and a medium degree of flexible leadership practices across the dimensions of organizational leadership, human leadership, flexible vision, and flexible communication. Faculty members perceive leaders as actively involved in promoting open communication, motivating and engaging in decision-making, and caring for staff needs. The analysis revealed a statistically significant positive relationship between flexible organizational leadership and academic freedom. The study showed that the dimensions of flexible vision and flexible communication had the strongest associations with academic freedom, highlighting the importance of adapting vision and improving communication channels to enhance faculty engagement and loyalty. Younger faculty members and more educated individuals tended to rate both leadership and academic freedom higher.